POLITICAL VIEW AND ORIENTATION OF THE ROHIS MEMBERS TOWARD THE FORM OF THE STATE - A.M Wibowo (Balai Penelitian dan Pengembangan Agama Semarang, 2017)
This study aims at describing the model of religious value transmission communication that occurs in Rohis organization as a form of Islamic proselytizing, at viewing the students’ view toward the form of the state government, and at viewing the political orientation of the Rohis members. By using the qualitative approach, this study has successfully gathered the following findings. First, the model of religious value transmission through the Rohis organization is the one way traffic communication. This transmission process involves communicators namely the mentor, the Rohis coaching teachers, da’i/mubaligh from values mass organization background (political parties and non-government organizations), and alumni. The internalization of such religious attitude has been conducted both verbally and non-verbally using the social media (WhatsApp, Instagram, Twitter, and Line). Second, the Rohis members had peculiar political view and orientation in relation to the leader and the form of the state. In relation to the leader, the Rohis members will vote for the male and Islamic leader. Then, in relation to the form of the state there are two groups among the Rohis members. One group demands the Unified State of Indonesian Republic (NKRI, Negara Kesatuan Republik Indonesia), while the other group demands the Islamic state. However, the supporters of the unified republic are quite bigger than those of Islamic state.